2012
DOI: 10.2355/isijinternational.52.168
|View full text |Cite
|
Sign up to set email alerts
|

Conformity between Mechanics and Microscopic Functions of Hydrogen in Failure

Abstract: Conformity between macro-mechanics and microscopic functions of hydrogen in failure is reviewed in reference to some models of hydrogen embrittlement (HE), focusing on the role of plasticity. Plastic strain localization, a characteristic feature of HE, is consistent with the hydrogen-enhanced creation of vacancies during plastic deformation. Constitutive relations that take into account the presence of voids describe well the ductile fracture process in HE. The effect of hydrogen on increasing the density of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Models describing vacancy formation processes are also used to describe the loss in mechanical properties in the presence of hydrogen. For instance, Nagumo et al [141] have described ductile fracture induced by vacancy clustering (leading to void formation) using a yield criterion originally developed for porous materials [63, 217]. They found that the values of the strain energy release rate (J-integral) in low-carbon steels are lower in the hydrogen-charged specimens, with an equivalent increase of 1.5% in the void volume fraction.…”
Section: Description Of the Failure Mechanisms Affecting Steelsmentioning
confidence: 99%
“…Models describing vacancy formation processes are also used to describe the loss in mechanical properties in the presence of hydrogen. For instance, Nagumo et al [141] have described ductile fracture induced by vacancy clustering (leading to void formation) using a yield criterion originally developed for porous materials [63, 217]. They found that the values of the strain energy release rate (J-integral) in low-carbon steels are lower in the hydrogen-charged specimens, with an equivalent increase of 1.5% in the void volume fraction.…”
Section: Description Of the Failure Mechanisms Affecting Steelsmentioning
confidence: 99%
“…Gen OGITA, 1,2) Koki MATSUMOTO, 1) Masahito MOCHIZUKI, 1) Yoshiki MIKAMI 3) * and Kazuhiro ITO 3) 1) Division of Materials and Manufacturing Science, Graduate School of Engineering, Osaka University, 2-1 Yamadaoka, Suita, Osaka, 565-0871 Japan.…”
Section: Numerical Simulation On Effect Of Microstructure On Hydrogenmentioning
confidence: 99%
“…However, several reports noted that this results to hydrogen cracking. 1) Stress and strain distribution 2) and its corresponding hydrogen diffusion behavior are strongly influenced by the microstructure morphology 3,4) of duplex stainless steels with heterogeneous structures composed of ferrite and austenite phases with different mechanical properties, hydrogen solubility, and hydrogen diffusion coefficient. However, stress and diffusible hydrogen concentration distribution are influenced by the microstructure and their effects on hydrogen cracking have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although duplex steel is often used under cathodic protection, numerous problems of hydrogen cracking have been reported. [1][2][3][4][5][6][7][8] Hydrogen solubility, hydrogen diffusion coefficient, stress/ strain distribution, 9) and the corresponding hydrogen diffusion behavior are considered to be strongly influenced 10,11) by the heterogeneous microstructure consisting of two phases with different mechanical properties. The factors influencing the behavior of diffusible hydrogen in duplex stainless steels…”
Section: Introductionmentioning
confidence: 99%